Neural mechanisms of social risk for psychiatric disorders - Meyer-Lindenberg, Andreas; Tost, Heike (Nature neuroscience, 2012)
Mental health and social life are intimately inter-related, as demonstrated by the frequent social deficits of psychiatric patients and the increased rate of psychiatric disorders in people exposed to social environmental adversity. Here, we review emerging evidence that combines epidemiology, social psychology and neuroscience to bring neural mechanisms of social risk factors for mental illness into focus. In doing so, we discuss existing evidence on the effects of common genetic risk factors in social neural pathways and outline the need for integrative approaches to identify the converging mechanisms of social environmental and genetic risk in brain.